Determination of Executive Information System: Data Warehouse, Business Intelligence and Brainware (Literature Review) - Marhadi Marhadi (Dinasti Publisher, 2023)
This literature review is themed on Determination of Executive Information System Data Warehouse, Business Intelligence, and Brainware, which is a scientific article that aims to compile a research hypothesis, namely the influence between variables so that it can be used for further research in the field of executive support systems for business. The writing of this article uses the literature review method or it can be called the library research method. This data is taken from articles such as Google Scholar, Google Scholar, the Mendeley application, which provides articles and scientific journals. The results of writing this article are 1) Information technology has an influence on the Executive Information System, 2) Business Intelligence has an influence on the Executive Information System and 3) Brainware has an influence on the Executive Information System. Outside the variables above also affect the endogenous variables of the Information System executive and there are many other factors that may influence the next variable.